2022
DOI: 10.3390/fermentation8070310
|View full text |Cite
|
Sign up to set email alerts
|

Altering Methane Emission, Fatty Acid Composition, and Microbial Profile during In Vitro Ruminant Fermentation by Manipulating Dietary Fatty Acid Ratios

Abstract: This study evaluated the effects of different dietary n-6/n-3 polyunsaturated fatty acid (PUFA) ratios on in vitro ruminant fermentation. Methane production, fatty acid composition, and microbial profiles were compared after the in vitro fermentation of rumen fluid collected from cows that had been fed isoenergetic and isoproteic experimental diets at three different n-6/n-3 ratios: 3.04 (HN6, high n-6 source), 2.03 (MN6, medium n-6 source), and 0.8 (LN6, low n-6 source). The fermented rumen fluid pH and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Low methane production at the seed bulking stage may come forth less in vitro fermentation (low total gas production) due to related to the increased lignin hemicellulose complex of the plant (Terrett & Dupree, 2019 ). Besides, low methane production at the seed bulking stage can be connected to the anti‐methanogenic property of the high level of oil content and ω−3 and ω−6 fatty acids at the seed bulking stage (Yilmaz and Kara, 2022b ; Sun et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low methane production at the seed bulking stage may come forth less in vitro fermentation (low total gas production) due to related to the increased lignin hemicellulose complex of the plant (Terrett & Dupree, 2019 ). Besides, low methane production at the seed bulking stage can be connected to the anti‐methanogenic property of the high level of oil content and ω−3 and ω−6 fatty acids at the seed bulking stage (Yilmaz and Kara, 2022b ; Sun et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the addition of fat to dairy cows' diets produces various changes in rumen fermentation, which are closely related to FA composition [17,31,32]. It has been reported [6] that adding excessive fat to the diet of dairy cows inhibits rumen fermentation, especially the addition of UFA, which has a more obvious inhibitory effect on rumen fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Sun et al [17] and Cui et al [18], gas chromatography (Agilent 6890N, Agilent Technologies, Inc., Beijing, China) determined the VFA concentrations of incubation fluid and the gas composition (CO 2 and CH 4 ) in gas samples. NH 3 -N concentrations in incubation fluid were measured by spectrophotometry according to Verdouw et al [19].…”
Section: Sample Collection Measurement and Calculationmentioning
confidence: 99%
“…Moreover, MCP content was analyzed following the method described by Makkar et al ( 1982 ). The gas chromatography (JC-7890, Juchuang Group Co., Ltd., Qingdao, Shandong, China) was utilized to analyze the VFA concentrations, including acetate, propionate, butyrate, isovalerate and valerate (Sun et al 2022 ). The non-glucogenic-to-glucogenic acids (NGR) ratio was calculated by NGR = (acetate + 2 butyrate + valerate) / (propionate + valerate) (Zhang and Yang 2011 ).…”
Section: Methodsmentioning
confidence: 99%